Sufistic Leadership Management of the Head in the Madrasah - Ervina Desilva; Suheri Suheri (Dinasti Publisher, 2024)
Every organization or institution needs to have good leadership management and teamwork. In this case, schools need to be led properly so that management can run well. The principal's leadership style and ability needs to be good, and of course every leader has his own leadership style and characteristics. Leaders who have religious ethics, who have a clean and peaceful heart (qalb al-munib wa qalb al-salim), have a healthy mind and strong body (aql salim wa jism al-salim), and can present God in their hearts them, thus making the soul calm (nafs al-mutmainnah) are some of the characteristics of Sufistic leaders who are considered capable of making a good management system. Therefore, this study aims to reveal the leadership style and characteristics of the principal of Madrasah Ibtidaiyah at-Taqwa Bondowoso, in order to find the pattern of sufistic leadership that is applied by him. A qualitative method with an analytical descriptive approach will be used in this study. This study succeeded in finding that the sufistic characteristics of the principal of Madrasah Ibtidaiyah at-Taqwa Bondowoso are implemented in the attitude of being patient, humble, sincere, istiqamah, wara' and responsible, all of which are acknowledged by administrators and students. So it is proven that the sufistic leadership style is able to produce good organizational and institutional management systems.